Tratamiento conservador de ameloblastoma uniquístico. Presentación de un caso - Vinitzky-Brener, Ilan (2022)
Ameloblastomas are the second most common odontogenic neoplasms, they are benign, however, they present an aggressive and locally infiltrative behavior, with a high recurrence rate; so its treatment is very controversial. We present the case of a 14-year-old male patient, with no relevant medical history, with increased volume in the posterior mandibular region left side, hard, with a color like the adjacent skin and painless on palpation. A puncture and an incisional biopsy were performed, obtaining as a histopathological result: mural unicystic ameloblastoma, which was treated conservatively with curettage and peripheral ostectomy, evolving favorably and rehabilitated with osseointegrated implants. Treatment modalities can be divided into radical and conservative. The technique to choose depends mainly on the type of ameloblastoma, followed by histology, its location, size and age of the patient; so each treatment must be studied and individualized.